Grocery shopping assistant for visually impaired / Ahmad Yusri Dak, Saadiah Yahya and Nik Mariza Nik Abdull Malik - Dak, Ahmad Yusri; Yahya, Saadiah; Nik Abdull Malik, Nik Mariza (Research Management Institute (RMI), 2008)
Providing a great shopping experience to shoppers is the most competitive strategy taken by every grocery owners. They are striving to satisfy the growing demands of todays savvy shoppers. Unfortunately, most ofthe grocery owner is not actively pursuing a solution to create an independent shopping environment to their customers who are blind and visually impaired people. The information printed at the grocery items make shopping independently impossible for the blind and very difficult for visually impaired people. This sensory capability limits their shopping activities in identifying items at the grocery store. There are many kinds of grocery items that can be identified by the means of touch or smell such as vegetables and fruits, but it is a challenging effort to differentiate packaged items. Therefore, blind shoppers must rely on assistance from sighted individual or grocery store employee to help them in getting the exact items which may be burdening and a waste oftheir time. This situation will restrict the independence movement ofthe blind shoppers. The Grocery Shopping Assistant was created to assist the blind in identifying grocery items during shopping using Radio-frequency Identification (RFlD) and text to speech technology. The blind only need to touch the RFID tag attached at the grocery item to the RFID scanner. The necessary product information regarding the item will be extracted from the database based on the primary key. This text-based information will be converted into a voice based and push to the user s hand phone via Bluetooth technology. The implementation of this system allows blind people to shop as efficiently and safely as anyone else without having to rely on anyone. This study also investigates user satisfaction of the system. The result exhibits that the users are very impressive with the shopping independence that this system can offer them.